Glory of Women in Family (Islamic Feminism Perspective) - Kholifatur Rosyidah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
Family is the basic foundation of the spread of Islam. In the family there is power that becomes control of the development of the family itself. Gender equality often occurs in a family, in this case the similarity between mother and father or commonly known as equality. In everyday life it is often disputed about the work of men and women that are expected to be in accordance with their nature. This view still revolves around biological factors where weak-bodied women should get light jobs while men who are physically strong should get jobs that show more power. This study focuses more on the glory of women in the family with an Islamic feminism perspective. This research method uses descriptive methods using a qualitative approach to describe data relating to the glory of women in the family. The research data is in the form of quotes, words, phrases, and story sentences. The source of the data in this study was the observation of several sakinah families in the Sidoarjo city area. The results of this study suggest that in Islam there is also an understanding of gender equality between men and women. This case is according to the instructions of the Qur'an and also Al-Hadist. There are also several rights for women to be glorified in their families. So women are not looked down on by their family members and are also not viewed negatively by family and society. Keywords: Family, Islam, Glory, Women, Feminism, Gender Equality, Qualitative Descriptions.